La liturgia cristiana como dinamizadora del tiempo (2016)
In Western societies, an increasingly marked phenomenon is being observed that consists of the loss of memory of the past and forgetting the future, to be anchored in an eternal present that specialists call “presentism”. This trend leads to disharmonize the lives of men, losing the perspective that a past can provide which in turn enables a present and opens to a future. The alternative to harmonize time is the liturgy that celebrates the Christian Mystery.